DEVELOPMENT OF INTERACTIVE PHYSICS LEARNING VIDEOS BASED ON SCIENCE ENVIRONMENT TECHNOLOGY SOCIETY AT THE HIGH SCHOOL LEVEL - Julia, Cut Rahma; Jannah, Misbahul; Rusydi, Rusydi; Hamid, Abdul (Universitas Islam Negeri Ar-Raniry, 2024)
This research is motivated by the use of learning methods that are still monotonous and uninteresting, the discussion of one of the physics materials that is difficult for students to understand, namely static fluid materials. This results in students having difficulty understanding the concepts and equations contained in static fluid materials. To overcome this problem, an interactive physics learning video based on the Science Environment Technology Society (SETS) was developed in order to provide students with an understanding of static fluid materials and become a digital media that can be used in the long term because it is flexible so that it can be used anywhere to repeat static fluid materials. The objectives of this research are: (1) To design interactive physics learning videos based on SETS at the high school/MA level; (2) To find out the feasibility of interactive physics learning videos based on SETS at the high school/MA level and (3) To find out the practicality of interactive physics learning videos based on SETS at the high school/MA level. This study uses the Research and Development (R&D) method based on the Alessi and Trollip development model. In this study, a product was produced in the form of interactive physics learning videos based on SETS. The results of the study show that SETS-based interactive physics learning videos have met the category of very feasible. This is determined based on the results of validation from media experts with a percentage of 90.4% included in the